Impact of Phone Reminders on Survey Response Rates : Evidence from a Web-Based Survey in an International Organization - Smets, Lodewijk (World Bank, Washington, DC, 2018)
This research note investigates the impact of phone reminders on response rates in the context of a web-based survey in an international organization, the World Bank. After randomly assigning treatment to 248 survey participants, the study finds an intention-to-treat effect of 19.86 percentage points. Given a relatively low treatment compliance rate (31 percent), the estimated average effect of treatment-on-the-treated is even larger, corresponding to an increase of 64 percentage points. Therefore, if ways can be found to increase treatment compliance, high response rates are attainable. This may lead World Bank surveyors to turn to sample surveys more often, reducing survey overload in the institution.